Media Convergence Strategy on Metro TV: Optimizing the Use of New Media in the OPSI Program - Maulianza, Medo; Ariestyani, Arleen; Ahdareni, Riana Jogi; Aprilianti, Limia (Universitas Ahmad Dahlan, 2022)
This study aims to determine Metro TV's media strategy in media convergence, especially in optimizing the use of new media for broadcast programs: